PENERAPAN GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI BLAJAR ANAK DENGAN HAMBATAN EMOSI DAN PERILAKU DI SLB E HANDAYANI - Rofiqoh Nur Istighfar, - (2019)
This study aimed to determine the effects of the use of gamification on learning motivation of children with emotional and behavioral disorder. The type of this research was an experiment research with one group pre test post test designs. Data collection was done by using observation instruments and questionnaires about learning motivation. The sampling in this study used probability sampling with lottery sampling techniques and obatained sampels used are children with emotional and behavioural disorder 7th grade as may as six students. The data analysis used non-parametric statistical techniques with the Wilcoxon Test. The results showed that the use of gamification strategies was influential in increasing learning motivation of children with emotional and behavioral disorder. Gamification could be applied as an alternative in increasing learning motivation of children with emotional and behavioral disorder. Keywords: emotional and behavorial disorder, gamification, learning motivation